2019
DOI: 10.1021/acsami.9b08289
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Large-Scale Flexible Optoelectronics Using Ultrathin Silver Films with Tunable Properties

Abstract: One key obstacle in fabricating efficient flexible and printable optoelectronic devices is the absence of ideal flexible transparent conductors with superior optical, electrical, and mechanical properties. Here, highperformance flexible transparent conductors are demonstrated using ultrathin (<10 nm) doped silver films, which exhibit an averaged visible transmittance of 80% without any antireflection coating, sheet resistance less than 20 Ω sq −1 , and mechanical stability over 1000 bending cycles. The conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 46 publications
2
47
0
Order By: Relevance
“…Consequently, Al atoms are easier to be immobilized on the SiO 2 surface, which contributes to an increased density of heterogeneous nucleation sites for Ag atoms and leads to the early stage formation of an ultrathin and smooth doped Ag film. In addition, similar growth characteristics have been observed in the initial growth stage of Ni‐doped Ag films by Zhang et al [ 140 ] As the film continues to grow, the small metal particles coalesce into larger ones. Compared to a pure Ag film, the particle size of an Al‐doped Ag film only increases slightly when the film thickness increases from 3 to 15 nm (Figure 11a,b).…”
Section: Fabrication Of High‐quality Ultrathin Metal Filmssupporting
confidence: 77%
See 1 more Smart Citation
“…Consequently, Al atoms are easier to be immobilized on the SiO 2 surface, which contributes to an increased density of heterogeneous nucleation sites for Ag atoms and leads to the early stage formation of an ultrathin and smooth doped Ag film. In addition, similar growth characteristics have been observed in the initial growth stage of Ni‐doped Ag films by Zhang et al [ 140 ] As the film continues to grow, the small metal particles coalesce into larger ones. Compared to a pure Ag film, the particle size of an Al‐doped Ag film only increases slightly when the film thickness increases from 3 to 15 nm (Figure 11a,b).…”
Section: Fabrication Of High‐quality Ultrathin Metal Filmssupporting
confidence: 77%
“…Doping an additive metal into the candidate metal through a codeposition process is an efficient approach for preparing high‐quality, ultrathin, and ultrasmooth metal films without any wetting layer. [ 46,137–141 ] As schematically illustrated in Figure a, a small amount of additive metal (denoted as X here, which can be Al, Cu, Ti, Ni, Cr, etc.) is codeposited with Ag, creating a X‐doped Ag film.…”
Section: Fabrication Of High‐quality Ultrathin Metal Filmsmentioning
confidence: 99%
“…Therefore, we have demonstrated a low-temperature PE-ALD deposition and post-deposition treatment of ultrathin plasmonic TiN that is substrate insensitive. Ultrathin plasmonic materials are advantageous for their use as transparent and flexible electrodes in optoelectronic devices, and key to the development of bendable and wearable systems [19,20], and ultrathin films with thicknesses approaching a few monolayers result in strong confinement that can result in quantum effects, such as nonlinearity [21]. Our work opens up potentials of investigating a CMOS compatible ultrathin plasmonic material for these applications.…”
Section: Discussionmentioning
confidence: 85%
“…Importantly, we introduced a hydrogen-plasma post-deposition treatment to further alter the optical properties of TiN while maintaining the thermal budget at the low temperature of 250 • C. We found that such plasma treatments greatly improved the metallic quality of the films, increasing the ε 1 slope by 1.3 times, from −0.015 to −0.021, on MgO and two times, from −0.012 to −0.024, on Si (100) for 11 nm thick films. Our work demonstrates the feasibility of developing metallic and plasmonic ultrathin TiN films with a PE-ALD deposition and post-deposition treatment that is substrate insensitive and with a low temperature of 250 • C. Our work opens up potentials of investigating a CMOS compatible ultrathin plasmonic material, which have been of interest for flexible transparent optoelectronic devices [19,20] and nonlinear optical applications [21,22].…”
Section: Introductionmentioning
confidence: 88%
“…SERS substrates are usually made of noble metal (Ag, Au, Cu) nanomaterials, which can excite local surface plasmon resonance (LSPR) to generate strong extinction and scattering spectra [7]. In particular, SERS substrates composed of Ag nanostructures exhibit better SERS performance [8].…”
Section: Introductionmentioning
confidence: 99%